2021
DOI: 10.1016/j.xjon.2021.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Postcardiotomy shock extracorporeal membrane oxygenation: Peripheral or central?

Abstract: Postcardiotomy shock (PCS) is poorly defined in the literature, but is broadly understood to mean circulatory failure after cardiac surgery necessitating mechanical circulatory support and high-dose inotropes. PCS occurs in 0.5% to 1.5% of all cardiac surgeries and is important to better understand because it has an in-hospital mortality rate >50%. 1,2 In the past there were a limited number of ways to support a patient in such profound cardiogenic shock, but today there are multiple mechanical circulatory sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Post-cardiotomy shock (PCS) is a clinical condition that remains poorly defined in the literature but implies a state of circulatory failure after cardiac surgery, necessitating high dosages of vasoactive medication, inotropes, and occasionally, mechanical circulatory support (MCS) [1]. The incidence of PCS in adult patients undergoing elective cardiac surgery is 2% to 6%, and more severe stages of PCS are associated with in-hospital mortality rates up to 90% [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-cardiotomy shock (PCS) is a clinical condition that remains poorly defined in the literature but implies a state of circulatory failure after cardiac surgery, necessitating high dosages of vasoactive medication, inotropes, and occasionally, mechanical circulatory support (MCS) [1]. The incidence of PCS in adult patients undergoing elective cardiac surgery is 2% to 6%, and more severe stages of PCS are associated with in-hospital mortality rates up to 90% [2].…”
Section: Introductionmentioning
confidence: 99%
“…It often begins with damage to the myocardium during cardiac surgery, the use of cardiopulmonary bypass, or cardioplegic myocardial arrest [4]. Insufficient myocardial protection or residual valvular dysfunction severely aggravates the situation and increases myocardial stunning, myocardial ischemia, ischemia-reperfusion injury, and left and/or ventricular pressure and/or volume overload, causing LCOS [1][2][3]. Additionally, a cascade of events can be set off, including inflammatory responses, neurohormonal activation, and endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCS is poorly defined in the literature, but it is broadly understood to mean circulatory failure after cardiac surgery which is resistant to inotropic support and/or an intra-aortic balloon pump (IABP), and which requires mechanical circulatory support (MCS) such extracorporeal membrane oxygenation (ECMO). ECMO may improve a patient’s physiological state when in cardiogenic shock by stabilizing hemodynamics and tissue metabolism, allowing the necessary time for regeneration of the heart muscle [ 5 , 6 , 7 , 8 ]. The available literature has little information on postcardiotomy shock in patients undergoing heart valve surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lack of data from randomized studies on these strategies does not allow an understanding of their potential benefits and harms in this critical setting. The optimal access site for arterial cannulation for VA-ECMO is one of the most controversial topics [4]. A meta-analysis by Mariscalco et al [5] showed that peripheral cannulation for postcardiotomy VA-ECMO was associated with decreased in-hospital mortality compared to central arterial cannulation.…”
Section: Introductionmentioning
confidence: 99%